Detection of Salmonella spp. by a loop‐mediated isothermal amplification (LAMP) method targeting bcfD gene. (1st December 2014) - Zhuang, L.; Gong, J.; Li, Q.; Zhu, C.; Yu, Y.; Dou, X.; Liu, X.; Xu, B.; Wang, C.
Abstract: In this study, we developed and validated a loop‐mediated isothermal amplification (LAMP) assay for Salmonella detection targeting bcfD gene, a conserved fimbrial operon gene existing in Salmonella . The Salmonella LAMP assay we developed successfully amplified 44 Salmonella strains (14 standard strains and 30 clinical isolates), but none of 9 non‐ Salmonella standard strains ( Proteus mirabilis, Listeria monocytogenes, Escherichia coli, Pseudomonas aeruginosa, Shigella flexneri, Shigella sonnei, Klebsiella pneumoniae, Campylobacter jejuni and Vibrio parahemolyticus ). The detection limit was 5 CFU of Salmonella pure culture or 200 CFU of artificially spiked faeces per reaction system (equivalent to 5000 CFU g −1 of faeces), and this method could directly detect Salmonella in chicken faeces free of pre‐enrichment in a reaction time of 25 min. Our experiments show that the LAMP method we developed is a rapid, sensitive, specific and practical method for Salmonella detection. The Salmonella LAMP assay can potentially serve as new on‐site diagnostics in the food and agricultural industries. Significance and Impact of the Study: A loop‐mediated isothermal amplification (LAMP) assay was established to detect Salmonella targeting bcfD gene, a conserved fimbrial operon gene. The detection limit was 5 CFU of Salmonella pure culture or 200 CFU of artificially spiked faeces per reaction system (equivalent to 5000 CFU g −1 of faeces), and this method could directly detect Salmonella in chicken faeces free of pre‐enrichment in a reaction time of 25 min. The Salmonella LAMP assay is a rapid, sensitive, specific and practical method for Salmonella detection and can potentially serve as new on‐site diagnostics in the food and agricultural industries.